In or Out of A Classroom?: An Ecological Understanding of Foreign Language Creative Writing - Emmas Mas Pupah; Junjun Muhamad Ramdani; Rahmat Rahmat (University of Muhammadiyah Prof. DR. HAMKA, 2019)
The present study examined the extent to which poetry writing from an ecological perspective based on nested ecosystems model can create an expressive and creative English language learning environment. Six intermediate level students with average age of 13 and 14 were recruited voluntary and participated in this study. Data were collected via photovoice, interview and students’ poetry. The data were qualitatively content analyzed based on (Bronfenbrenner, the ecology human development, 1979) nested ecosystem model and the emergence of learners’ creativity was categorized first at the level of microsystem. Second, at the level of mesosystem, to analyze students activity photovoice SHOWeD questions (Wang, Yi, Tao & Carvano, 1998) was used. This study showed poetry writing in two nested ecosystem could create an expressive and creative English learning which provide the students with extended learning environment. These two diverse ecosystem levels brought different critical creativity and self expression. The findings contributed as the evidence of the ecological understanding of the pattern and variables involved in poetry writing as s platform for learning and write creatively.